Uber happy? Work and well-being in the “gig economy” - Berger, T; Frey, CB; Levin, G; Danda, SR (Oxford University Press, 2019)
We study the rise of the so-called “gig economy” through the lens of Uber and its drivers in the United Kingdom. Using administrative data from Uber and a new representative survey of London drivers, we explore their backgrounds, earnings, and subjective well-being. We find that the vast majority of Uber drivers are male immigrants, primarily drawn from the bottom half of the London income distribution. Most transitioned out of permanent part- or full-time jobs and about half of drivers’ report that their incomes increased after partnering with Uber. After covering vehicle operation costs and Uber’s service fee, we estimate that the median London driver earns about £11 per hour spent logged into the app. But while Uber drivers remain at the lower end of the London income distribution, they report higher levels of life satisfaction than other workers. Consistent with a trade-off between evaluative and emotional well-being observed among the self-employed, they also report higher anxiety levels. We hypothesize that the higher life satisfaction among Uber drivers partly reflects their preferences for flexibility and the autonomy that the platform offers. We provide suggestive evidence showing that drivers who emphasize flexibility as an important motivation to join Uber also report higher levels of subjective well-being. However, a minority of drivers who report that they would prefer work as an employee report lower levels of life satisfaction and higher levels of anxiety. Overall, our findings highlight the importance of non-monetary factors in shaping the welfare of workers in the gig economy.